One Health workers: innovations in early detection of human, animal, and plant disease outbreaks - Michael Wilkes; Sophia Papageorgiou; Tae Youn Kim; Loinda Baldrias; Edna Aguilar; Terra Kelly; Michael Tee (Inishmore Laser Scientific Publishing Ltd, 2019)
The majority (60%) of human pathogens are zoonotic and 75% of emerging zoonotic pathogens are from wildlife species (eg, Ebola, Zika). In addition, vector, water, and food-borne diseases greatly impact people, livestock, and agriculture and result in adverse effects on local, national, and global economies. Continuous monitoring and surveillance of newly emerging diseases and pandemic outbreaks is a critical component in One Health (OH) which is the term representing the collaboration of multiple disciplines working to achieve optimal health for people, animals, plants/crops, and the environment. For decades a group of minimally trained local workers --community health workers -- (CHWs) have functioned at the interface between community members and whatever health care system existed within a country. Today, around the world CHWs have become the bedrock and frontline health care providers as they deliver or monitor human treatments, engage in the detection of common illness, and offer preventive care. In these same communities there is often severely limited access to veterinary health services which has a negative impact on livestock production with implications for food security, and has led to the inappropriate and indiscriminate use of antibiotics. In rural areas poor field maintenance and common agricultural health problems results in the death or decreased crop production of important food sources. Inappropriate use of pesticides and other products that are toxic to animals and humans often enter the soil or water supply through misuse. This lack of health integration across human, animal, plant, and environmental health sectors in an ever-shrinking world begs for a shift in health services and the creation of a community based One Health Worker.